Law and Ethics in The Use of Information Technology: A Study on Privacy and Data Security - Muhammad Abdurrohman Sholih; Rika Santina (Journal of Law, Society and Living Norms, 2025)
This paper critically analyzes Indonesia's legal and ethical framework for privacy and data security amid rapid digital transformation, using a juridical-normative approach and case studies to evaluate the effectiveness of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) in addressing contemporary challenges. The research addresses a significant paradox where Indonesia's accelerating digital economic growth and high internet penetration contrast sharply with escalating cyber threats reported by the National Cyber and Encryption Agency (BSSN) and increasing large-scale data breach incidents causing public concern. The central research question examines: To what extent is the PDP Law effective in protecting citizens' privacy and data security in Indonesia's digital transformation era, and what are the key legal, technical, and ethical challenges that hinder its optimal implementation? The analysis examines key PDP Law provisions, comparing them with the EU's General Data Protection Regulation (GDPR) as a global benchmark, while presenting case studies of major data breaches at Tokopedia (2020), BPJS Kesehatan (2021), and the General Elections Commission (2023) to illustrate gaps between regulatory frameworks and practical implementation. The discussion extends to complex ethical dilemmas including state digital surveillance and AI-driven personal data analysis threatening citizens' privacy rights. Findings reveal that while the PDP Law establishes a strong legal foundation and represents a significant milestone, its effectiveness remains limited by weak enforcement, institutional cybersecurity vulnerabilities, and unresolved ethical issues, leading to strategic recommendations for government, organizations, and the public to collectively build a comprehensive, adaptive, and sustainable national data protection ecosystem for future digital challenges.